Development of random pulse width modulation technique for voltage source inverter drives - Luong, Quoc Dat; Nguyen, Manh Duc; Huynh, Minh Khoi; Nguyen, Phu Cong; Phan, Quoc Dung (Institute of Advanced Engineering and Science, 2025)
In this research, the structure selection of the carriers in the implementation of random pulse width modulation (RPWM) method for single-phase voltage source inverter (VSI) drives is specified by a 16-bit binary sequence. Subsequently, the genetic algorithm (GA) is used to find the solution of the optimal sequence allowing the output voltage signal to achieve the minimum total harmonic distortion (THD). In addition, the harmonic spreading factor (HSF) is further analyzed to evaluate the acoustic noise and electromagnetic interference (EMI) of the operation of electromechanical system. Finally, through hardware testing process, the simulation results are validated in order to ensure the reliability of our research findings. The main components of this testing process are LAUNCHXL-F28379D utilized to generate controlling pulses for the modules insulated gate bipolar transistors (IGBT), and two EVAL-1EDI60I12AF gate driver modules for realizing the full-bridge inverter.